REFLEKSI PEMBELAJARAN ONLINE MAHASISWA DIFABEL NETRA DI MASA PANDEMI COVID-19 - Astri Hanjarwati; Aulia Rahmi; Mawar Rahayuning Astuti; Sinta Ristiyanti (UIN Sunan Kalijaga, 2023)
The existence of a pandemic requires education to transform face-to-face learning into online learning. This condition forces all elements to adapt quickly, including students with visual impairments. This study aims to explore the experiences of students with visual disabilities during online learning during the pandemic. A qualitative research approach with a descriptive case study method was chosen as the approach in this study. Research data was collected by conducting structured interviews with open questions to 15 students with visual disabilities at UIN Sunan Kalijaga. The data that has been collected is then analyzed using thematic analysis according to Braun and Clarke, namely re-reading the data, coding, searching for themes, reviewing themes, determining a definite theme, and writing the results of the analysis. Data validity uses re-checking of information to respondents. The findings reveal that students with visual disabilities have had various experiences, both negative and positive experiences while carrying out online learning during the pandemic. The results of this study emphasize educational institution stakeholders to involve the voice and participation of students with visual disabilities in designing learning to have adequate accessibility.